Effectiveness of toric intraocular lens implantation for correcting irregular corneal astigmatism in cataract eyes - Xiteng Chen; Yuanfeng Jiang; Nan Gao; Yichen Gao; Jun Yang; Shaochong Bu; Fang Tian (Scientific Reports, 2024)
Abstract A retrospective cohort study was conducted to observe the correction effect of Toric intraocular lens (IOL) implantation in cataract eyes with specific types of irregular corneal astigmatism. Thirty-four eyes with either the "asymmetric bow-tie" pattern (Type I) or the "angled bow-tie" pattern (Type II) were included. Corneal topography was assessed using Pentacam HR, and changes in preoperative corneal astigmatism, visual acuity, manifest refraction, and objective visual quality were measured and compared. The average uncorrected distance visual acuity improved significantly from 0.86 ± 0.40 logMAR to 0.22 ± 0.15 logMAR (P < 0.001). Preoperative corneal astigmatism of 2.05 ± 0.90 D was corrected to a postoperative residual astigmatism of 0.78 ± 0.57 D (P < 0.001), with 32% of eyes within 0.50 D. The residual astigmatism prediction errors in Type I and Type II cases were (0.97 ± 0.68 D) and (0.66 ± 0.37 D), respectively (P = 0.100). The mean spherical equivalent prediction error in Type II cases (0.07 ± 0.36 D) was significantly smaller than that in Type I cases (− 0.29 ± 0.52 D) (P = 0.030). This study concludes that Toric IOL implantation effectively corrects specific types of irregular corneal astigmatism in cataract surgery. Eyes with the "angled bow-tie" pattern show higher accuracy in refractive predictions compared to eyes with the "asymmetric bow-tie" pattern.